2020
DOI: 10.18502/japh.v5i2.4243
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution sources in Ahvaz city from Iran

Abstract: Human needs clean and healthy air. Clean air is more important than food and water. Industries and industrial activities produce a lot of gases and particles that pollute the air. Air pollution, as one of the concerns of the present age, in addition to environmental degradation and economic damage, poses serious risks to human health. Continuous monitoring of air quality to identify pollut- ants and identify sources of their emissions is also one of the basic strategies for controlling air pollution. Unhealthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Various industrial activities in Ahvaz (e.g., extraction and refining of oil and gas, petrochemical industries, and steel industry) cause the emission of contaminants to the environment (Goudarzi et al, 2018;Effatpanah et al, 2020). Specifically, the oil industry, traffic, dust storms (Velayatzadeh, 2020), and <10 µm particles and ozone are problematic in Ahvaz (Hosseini et al, 2017). Ahvaz was once classed among the 10 cities with the worst air quality, based on the World Health Organization report in 2010, and has had episodes of acid rain (The Observer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various industrial activities in Ahvaz (e.g., extraction and refining of oil and gas, petrochemical industries, and steel industry) cause the emission of contaminants to the environment (Goudarzi et al, 2018;Effatpanah et al, 2020). Specifically, the oil industry, traffic, dust storms (Velayatzadeh, 2020), and <10 µm particles and ozone are problematic in Ahvaz (Hosseini et al, 2017). Ahvaz was once classed among the 10 cities with the worst air quality, based on the World Health Organization report in 2010, and has had episodes of acid rain (The Observer, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The use of heavy-duty diesel (HDD) equipment for the construction and maintenance of transportation infrastructure is the main contributor to the increasing air pollution problem. This affects both economic and social issues (Ugwu et al, 2020). One of the main pollutants that threaten human health is dust, which is typically produced during building activities and pollutes the surrounding areas (Ayarkwa et al, 2014).…”
Section: Effect Of Construction Activities On Residentsmentioning
confidence: 99%
“…Major industries such as the steel and oil industry and drilling and oil extraction activities contribute signi cantly to Ahvaz's air pollution. In addition to industry (Velayatzadeh 2020), it was reported that In the winter months (November through February), the particular matter concentration was higher than in the spring and summer months (March through October). (Goudarzi et al 2021).…”
Section: Ozone (O 3 )mentioning
confidence: 99%